(untitled) (AYUSHDHARA, 2025)
In this present case study, a 24-year-old female patient consulted the Ayurvedic OPD with pain in the lower abdomen, irregular menses, burning maturation, nausea, loss of appetite from last 2-3wks. She was advised for ultrasonography (USG) and the findings suggested a left ovarian haemorrhagic cyst measuring 4.5cm x 3.7cm. She was supposed to be treated with traditional ayurvedic formulations; but the case was treated for three months with a combination of different traditional Ayurvedic drugs, with the goal of relieving symptoms and dissolving the ovarian cyst. This patient was treated with traditional Ayurvedic formulations like Prabhakar vati, Trivrita avleha, Haritki churana, Triphala guggul, Kanchanar guggul, Phalatrika and Varunadi Kwatha, Syp Evecare forte + Evecare capsule. Only traditional Ayurvedic medicines were used during the course of the treatment. Patient’s condition was assessed through USG after six months of treatment for ovarian cyst which was completely relieved. Therefore, this study was conducted to evaluate one of the treatment regimens for ovarian cyst.